Senecionina do Senecio brasiliensis reduz a expressão de genes induzidos por interferon em células do corpo lúteo in vitro - Lasta, Caroline Raquel Poglia (2024)
Maternal recognition of pregnancy is a crucial period for the maintenance of gestation in bovine females, mediated by interferon-tau (IFNT). Senecio brasiliensis, a highly resistant plant found in South America, parts of North America, and particularly in southern Brazil, contains pyrrolizidine alkaloids that can cause hepatic intoxication when metabolized into pyrroles in the liver. Recent studies have shown that animals intoxicated by Senecio exhibit ovarian alterations, which may contribute to cases of subfertility in cattle in southern Brazil. To investigate these issues, genes involved in bovine maternal recognition of pregnancy, the HIPPO signaling pathway (a key cell proliferation pathway), and apoptotic genes were evaluated using an in vitro luteal cell culture protocol. Ovaries from cows in the diestrus phase were obtained from a slaughterhouse for the experiments. Four treatment groups were established: a control group with no treatment, a group treated with 1 µg/ml of IFNT, a group treated with 1 µg/ml of IFNT and 10 ng/ml of senecionine, and a group treated with 1 µg/ml of IFNT and 100 ng/ml of senecionine. Results indicated that senecionine alters the ability of luteal cells to signal the embryo, thereby affecting the mechanism of maternal recognition of pregnancy driven by IFNT. Furthermore, progesterone synthesis was disrupted, and both the proliferative activity and apoptotic mechanisms of luteal cells treated with senecionine were affected. These findings highlight the detrimental impact of Senecio brasiliensis on reproductive health in cattle.